Langka-We Pledge: Solution for Travelers’ Sustainable Behaviors - Izzuddin, Muhammad Zul Amri Izzuddiin; Anggrecke Valentina Yuricka; Farida Rahmany (Multidisciplinary Applied Research and Innovation, 2023)
Abstract : Globalization has enabled people to move from one country to another easily and helped accelerate the growth of the tourism industry. The economic benefit from tourism has to balance with environmental well-being. As environmental quality strongly depends on human behavior patterns, it is important to control tourist behavior at a tourism destination. This paper proposes practical policy innovation for attracting tourists with more sustainable behavior as well as improving those with low sustainability through a pledge, named “The Langka-We Pledge”. We discuss how the implementation of a pledge can have a significant positive impact in promoting sustainable tourism. Keywords: Sustainable Tourism, Tourist Behavior, Travel Pledge, Environmental Awareness